2018
DOI: 10.1002/cche.10032
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of durum wheat (Triticum Turgidum Subsp Durum) during malting process

Abstract: Background and objectives Effects of 45 and 70°C final malt drying temperature on a traditional Italian durum wheat (SM45, SM70) were evaluated for the malt quality parameters and the wort characteristics when employed in rate of 40% with commercial barley malt (BM), using a common wheat (CWM) as a control test. Findings Drying temperatures and wheat genotypes were major contributors to variability in malt quality parameters. SM45 and SM70 were characterized by reduced protein and starch degradation, lower sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
2
5
1
Order By: Relevance
“…According to Faltermaier et al , most of the characteristics of the malt obtained from ‘Senatore Cappelli’ were in the range suggested for good quality wheat malt, in terms of moisture, total protein, viscosity and extract. Levels of α ‐amylases and diastatic power were reported to be relatively high, in agreement with the observations of Briggs and Alfeo et al , who reported that the contents of these enzymes were normally in excess in wheat malt, and were twice as high as in durum wheat when compared with common wheat. Viscosity, extract and nitrogen compounds (i.e.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…According to Faltermaier et al , most of the characteristics of the malt obtained from ‘Senatore Cappelli’ were in the range suggested for good quality wheat malt, in terms of moisture, total protein, viscosity and extract. Levels of α ‐amylases and diastatic power were reported to be relatively high, in agreement with the observations of Briggs and Alfeo et al , who reported that the contents of these enzymes were normally in excess in wheat malt, and were twice as high as in durum wheat when compared with common wheat. Viscosity, extract and nitrogen compounds (i.e.…”
Section: Resultssupporting
confidence: 90%
“…A high protein content is detrimental in brewing, as it can cause fermentation problems . In this respect, the 11.4% protein content of ‘Senatore Cappelli’ was very similar to that of the durum wheat variety ‘Simeto’, which was also proposed for brewing by Alfeo et al . Furthermore, the high germinability of the grain of ‘Senatore Cappelli’ is consistent with the economic sustainability of the malting process.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations